Text presentation or video: Malaysian university students' preferences with synchronous and asynchronous learning - Azar, Ali Sorayyaei; Tan, Nur Haslinda Iskandar (Education and information technologies, 2023)
In overcoming the obstacles of online learning with the current Covid-19 pandemic crisis, synchronous and asynchronous learning has been a significant part of teaching strategies applied by educators to construct a collaborative online environment with Malaysian university students. Synchronous learning has always been the most effective strategy for social learning, while asynchronous learning allows students to learn on their own schedule. Moreover, despite having many educational platforms created for higher educational settings, the practicality of selection between two teaching–learning approaches of text-presentation and video is still a debate among teachers/ lecturers with students’ learning styles. Therefore, this paper explored Malaysian university students’ preferences between synchronous and asynchronous learning modes with text-presentation or video. Qualitative and quantitative data from 178 participants from both public and private universities were collected via open and close-ended questions in the designed questionnaire. The findings indicated that 68% of the students preferred synchronous learning mode compared to asynchronous. Meanwhile, 39% of the students favoured both text-presentation and video learning tools to be implemented in synchronous and asynchronous approaches as it provided them better opportunities to grasp the learning content better. Thus, it can be concluded that the synchronous learning mode is preferred if only one method is provided as the students highly value the teacher’s presence for ease of communication, but students prefer a range of delivery methods. Moreover, the students also displayed a strong preference for applying both text-presentation and video to achieve their learning outcomes. Thus, it is suggested that the university lecturers need to explore and apply interactive pedagogical methods in online teaching-learning process, while contributing to the development of motivation, participation, and engagement among the university students in acquiring their subjects. As such, the findings of this study have informed the pedagogical implications, and further studies are mandatory.